The mechanism of action and the active center of pepsin. - Yuan, Chi-Yang. (University of Ottawa (Canada), 1960)
The C14-labelled synthetic substrates, carbobensoxy-L-glutamyl-L-tyrosine and its ethyl ester were synthesised by the condensation of carbobenzoxy-L-glutamic anhydride and L-tyrosine ethyl ester. C14glutamic acid and C14 tyrosine were used in these syntheses giving substrate molecules labelled in the glutamic acid moiety or in the tyrosine moiety. The various radioactive substrates were incubated at pH 4.0 with pepsin. After a given period of time, the pepsin was isolated from the incubation mixture and found to be radioactive only when substrates containing C 14-tyrosine were involved. This radioactive protein was found to liberate C14-tyrosine ethyl ester upon incubation in acid solution. These facts were taken as evidence that the radioactive protein isolated is an intermediary complex pepsin-tyrosine ethyl ester formed during the hydrolysis of the peptide derivative by the proteolytic enzyme. A mechanism is proposed to explain the formation of such a complex. After partial acid hydrolysis of this radioactive complex, paper chromatography and paper electrophoresis were used to isolate a radioactive peptide. The amino acid composition of this peptide was found to be the following: alanine, aspartic acid, serine, glutamic acid, threonine, glycine, arginine, valine, tyrosine and leucine. We claim that this peptide represents part of the active center of pepsin.
Keywords: Chemistry, Biochemistry.